2013
DOI: 10.1016/j.dsr.2012.12.012
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial biodiversity in deep-sea sediments from two regions of contrasting surface water productivity near the Crozet Islands, Southern Ocean

Abstract: biodiversity in deep-sea sediments from two regions of contrasting surface water productivity near the Crozet Islands, Southern Ocean., Deep-Sea Research I, http://dx.doi.org/10. 1016/j.dsr.2012.12.012 This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resulting galley proof before it is published in its final citable f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 82 publications
(91 reference statements)
2
16
0
Order By: Relevance
“…These clades seemed to be also dominant in the surface sediments along the Antarctic Polar Front. Gammaproteobacteria might be particularly important in Arctic (Bienhold et al, 2011;Ravenschlag et al, 1999) and Antarctic sediments (Carr et al, 2013;Jamieson et al, 2013), which is also indicated by our study. However, the data on key clades in deep-sea sediments is becoming sparser with increasing phylogenetic resolution.…”
Section: Active Microbial Communities In Abyssal Sediments Of the Sousupporting
confidence: 73%
See 1 more Smart Citation
“…These clades seemed to be also dominant in the surface sediments along the Antarctic Polar Front. Gammaproteobacteria might be particularly important in Arctic (Bienhold et al, 2011;Ravenschlag et al, 1999) and Antarctic sediments (Carr et al, 2013;Jamieson et al, 2013), which is also indicated by our study. However, the data on key clades in deep-sea sediments is becoming sparser with increasing phylogenetic resolution.…”
Section: Active Microbial Communities In Abyssal Sediments Of the Sousupporting
confidence: 73%
“…The standing stocks of benthic meioand macrofaunal assemblages of the Southern Ocean further suggest a relatively high supply of POC to the sediments (Brandt et al, 2007). Interestingly, in the Southern Ocean, benthic communities of regions with high surface water productivity were found to be similar to those in low productivity regions (Jamieson et al, 2013) and in sediments below the Ross ice-shelf (Carr et al, 2013), indicating that other factors than just the extent of primary productivity play a role. However, as research focused on macrofaunal benthic communities, little is known about microbial communities in sediments along the Antarctic Polar Front.…”
Section: Introductionmentioning
confidence: 88%
“…However, these results should be compared with caution due to the variation in molecular techniques employed and biases in DNA extraction and PCR amplification protocols that may over-or under-represent certain taxa (Al-Awadhi et al, 2013;Hazen et al, 2013). Overall, proteobacteria, particularly belonging to the α-, γ-and δ-classes are the most abundant taxa in molecular surveys of DSSs microbial communities (Li et al, 1999;Nercessian et al, 2005;Xu et al, 2005;Zeng et al, 2005;Jiang et al, 2007;Pachiadaki et al, 2011;Jamieson et al, 2013;Wu et al, 2013). ϒ-Proteobacteria were the most abundant group in the midAtlantic ridge's Rainbow hydrothermal vent (≈ 50% of total OTUs) (Nercessian et al, 2005), the Pacific Ocean Fe(III)-Mn(IV) nodules (≈ 70% of clones) (Xu et al, 2005) and the Western Pacific Warm Pool sediments (≈ 45%) (Zeng et al, 2005).…”
Section: Features Referencesmentioning
confidence: 95%
“…δ-Proteobacteria were the most abundant group in cold seeps in the Japan Trench (6200 m) (Li et al, 1999) and ε-Proteobacteria, along with γ-and α-Proteobacteria, composed the majority of sequences from some deep sea hydrothermal vent systems (Moyer et al, 1995(Moyer et al, , 1998Reysenbach et al, 2000). Other relatively abundant taxa include the Cytophaga/Flavobacteria/ Bacteroidetes group (Li et al, 1999;Nercessian et al, 2005;Xu et al, 2005;Zeng et al, 2005;Martín-Cuadrado et al, 2007), Planctomycetes (Nercessian et al, 2005;Zeng et al, 2005;DeLong et al, 2006;Martín-Cuadrado et al, 2007;Jamieson et al, 2013;Wu et al, 2013), Chloroflexi (mainly affiliated with Dehalococcoidetes (Inagaki and Nakagawa, 2008)) (DeLong et al, 2006;Martín-Cuadrado et al, 2007;Pachiadaki et al, 2011), Acidobacteria (Martín-Cuadrado et al, 2007;Wu et al, 2013), Firmicutes (Li et al, 1999;Zeng et al, 2005;Martín-Cuadrado et al, 2007), CFB group (Xu et al, 2005;Zeng et al, 2005), JS1 candidate division (previously joined with the OP9 candidate division) (Inagaki et al, 2003(Inagaki et al, , 2006Inagaki and Nakagawa, 2008) and Actinobacteria (Jamieson et al, 2013;Wu et al, 2013). Functions such as sulfate reduction in hydrothermal vents and cold seeps have been mainly attributed to ε-and δ-Proteobacteria (Desulfococcus and Desulfosarcina) (Longnecker and Reysenbach, 2001;Inagaki et al, 2002;Zeng et al, 2005), sulfur oxidation to γ-and ε-Proteobacteria …”
Section: Features Referencesmentioning
confidence: 99%
“…Benthic (seafloor-hosted) microbial communities of the ocean are very distinct from pelagic (seawater-hosted) communities (9) and are impacted by water depth (11,12), sediment depth (13,14), and by energy availability in the form of deposited organic matter (12,15,16). Marine sediments are known to host communities as diverse as those found in soils, with pronounced community turnover on small (decimeter to kilometer), intermediate (hundreds of kilometers), and large (thousands of kilometers) spatial scales (17,18).…”
mentioning
confidence: 99%